2008
DOI: 10.1590/s0001-37652008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the antimicrobial substances produced by Solanum palinacanthum (Solanaceae)

Abstract: To find out natural antimicrobial agents as alternative in therapeutics and to preserve food, the methanol extract of Solanum palinacanthum aerial parts was submitted to purification steps guided by antibacterial and antifungal assays. As a consequence, the flavonoid rutin and 3,5-dicaffeoylquinic acid were isolated by column chromatography and high performance liquid chromatography, and identified by mass and nuclear magnetic resonance spectrometry. Minimal inhibitory concentrations (MIC) of the quinic acid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
1
8
0
2
Order By: Relevance
“…3,5‐dicaffeoylquinic acid ( 4 ) was inhibiting all microorganisms tested, while 1,3‐dicaffeoylquinic acid ( 5 ) produced a wider inhibition zone in the yeast than against bacteria, especially E. faecalis and P. aeruginosa . The results obtained with phenolic acids agree with previous reports on the antimicrobial activity by these compounds .…”
Section: Resultssupporting
confidence: 91%
“…3,5‐dicaffeoylquinic acid ( 4 ) was inhibiting all microorganisms tested, while 1,3‐dicaffeoylquinic acid ( 5 ) produced a wider inhibition zone in the yeast than against bacteria, especially E. faecalis and P. aeruginosa . The results obtained with phenolic acids agree with previous reports on the antimicrobial activity by these compounds .…”
Section: Resultssupporting
confidence: 91%
“…Morin and rutin alone had no activity against MRSA but in combination showed antibacterial activity against said bacteria. In similar studies flavonoids combinations and their metallo-combinations show activity against various microbes [26,27]. Morin alone has been found to be active against Salmonella enteritidis with MIC of 150 μg/ml and B. cereus with MIC of 300 μg/ml.…”
Section: Discussionmentioning
confidence: 94%
“…Against a range of fungi of the genus Aspergillus, Weidenbörner et al (1990) reported little activity for quercetin and naringenin. Pereira et al (2008) observed in A. ochraceus that the MIC value for rutin was 35 mg/l.…”
Section: Discussionmentioning
confidence: 98%